Design av förarmiljö : Interiör för slaggtruck SH 60 med fokus på ergonomi och säkerhet - Aneer, Felicia; Hansols, Carl (2016)
Construction equipment and heavy machines for the industry are often designed with focus on theindustrial purpose. The metal industry in particular, is a heavy and rough industry where sometimes worker needs are set aside to prioritize the mechanical functions of the machines. As industrial design engineers, our role is to combine the needs of human, the demands of the industry and the the conditions of the producer when designing new products.This master thesis focuses on designing the driver environment in a slag hauler, a machine transporting slag in smelters. The slag hauler is produced by the company Kiruna Utility Vehicles (KUVAB), on their production site in Kiruna. A slag hauler is a low series product, and the manufacturing time is about one year. The driver environment on todays slag hauler have not been updated for a long time and the objective of this project has been to deliver a concept for a new driver cabin with improved ergonomics, safety and user experience. The goal was to deliver a concept that was implementable in 2017. The concept should be delivered as a CAD model and also a full size prototype.The project has been conducted using a human centred design approach, meaning that stakeholders have been involved throughout the whole process to ensure a design beneficial to all stakeholders. Through design methods applied in the right stage of the process, we have managed to tackle the design task of the complex product in an efficient way.The result is a cabin designed for the 5th-95th percentile of the population that embraces the importance of safety in terms of fire. The cabin has not only integrated all equipment in a nice, serviceable and producible way. It also enables KUVAB to change parts of the interior over time to create business possibilities as future customers can update/upgrade parts of the interior after delivery.By designing according to international standards, aspects of both ergonomics and safety are well thought through, which in the long term likely contribute to reduced ...